Encyclopedia of Analytical Chemistry 2010
DOI: 10.1002/9780470027318.a9135
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Power Applications with Conductive (Carbon‐Loaded) Composite Polymer Electrodes—Requirements and Characterization

Abstract: Pulsed power (PP) is a technology where energy is released to a load in a short time. Every device using this technology needs electrodes to transfer the electric energy to the load. Recent developments in composite conductive polymers make them suitable as electrodes for new or existing PP applications, where normally metals were used. Composite polymers, consisting of conductive filler and a nonconductive matrix, can solve several specific problems in common and to be developed (PP) applications, due to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…2008). Scanning resistive probe microscopy showed that only ∼2% of the surface area of the film is electrically conductive (Roodenburg et al . 2010b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2008). Scanning resistive probe microscopy showed that only ∼2% of the surface area of the film is electrically conductive (Roodenburg et al . 2010b).…”
Section: Methodsmentioning
confidence: 99%
“…Another cause that may limit higher inactivation rates is the composite character of the plastic packaging material. These materials have a partly electrical conductive surface and, consequently, close to the material surface, a nonhomogeneous electric field distribution occurs (Roodenburg et al . 2010b).…”
Section: Introductionmentioning
confidence: 99%